Expression patterns of peroxiredoxin genes in bronchial epithelial cells exposed to diesel exhaust particles - Seriani, Robson; Paula, Carla Peres de; Cunha, Anderson Ferreira da; Oliveira, Marcos Antonio de [UNESP]; Krempel, Paloma Gava; Frias, Daniela Perroni; Negri, Elnara Marcia; Mauad, Thais; Macchione, Mariangela (Elsevier, 2021)
Several mechanisms have been suggested to explain the adverse effects of air pollutants on airway cells. One such explanation is the presence of high concentrations of oxidants and pro-oxidants in environmental pollutants. All animal and plant cells have developed several mechanisms to prevent damage by oxidative molecules. Among these, the peroxiredoxins (PRDXs) are of interest due to a high reactivity with reactive oxygen species (ROS) through the functioning of the thioredoxin/thioredoxin reductase system. This study aimed to verify the gene expression patterns of the PRDX family in bronchial epithelial airway cells (BEAS-2B) cells exposed to diesel exhaust particles (DEPs) at a concentration of 15 μg/mL for 1 or 2 h because this it is a major component of particulate matter in the atmosphere. There was a significant decrease in mRNA fold changes of PRDX2 (0.43 ± 0.34; *p = 0.0220), PRDX5 (0.43 ± 0.34; *p = 0.0220), and PRDX6 (0.33 ± 0.25; *p = 0.0069) after 1 h of exposure to DEPs. The reduction in mRNA levels may consequently lead to a decrease in the levels of PRDX proteins, increasing oxidative stress in bronchial epithelial cells BEAS-2B and thus, negatively affecting cellular functions.
Keywords: Air pollution; BEAS-2B; Diesel exhaust particles; Oxidative stress; Peroxiredoxins